DEVELOPMENT OF INVESTMENT IN INDONESIA - Nita Ria Angkasa (PRANATA HUKUM, 2017)
Judging from the division of European Law (Civil Law) we know that is Public Law and Private Law. What is a "Public Law"? Public Law is a Law that discusses about public interest concerning the interest of the State. related to the problems in the discussion of this journal. Discussion of Indonesian Legislation Regulation in Indonesia that is After Independence (1945 to present) Beginning of Legislation with Regulatory Sequence: TAP MPRS Number XX / MPRS / 1966 Jo TAP MPR Number V / MPR / 1973 and TAP NO IX / MPR / 1978, TAP MPR NO.III Year 2000, Law No. 10 of 2004 on Laws and Regulations No. 12 Year 2011 and the Role of Government Institutions to the Implementation of Laws Regulations in Indonesia Regarding Institutions The establishment of the law itself is contained in Article 5 paragraph (1) of the 1945 Constitution, Article 21 and Article 20 so that the holder of the main legislator is the DPR. Based on Article 5 paragraph (1), the President shall be entitled to submit a draft Law to the House of Representatives. Paragraph (2) The President shall stipulate a Government Regulation to enforce the Act as appropriate.